Convective Drying and Mathematical Modeling of Onions Dried Using a Flat Plate Solar Air Heater - Hanif, Muhammad; Rahman, Masood Ur; Amin, Muhammad; Khattak, Mansoor Khan; Ramzan, Muhammad; Ud Din, Subhan; Khan, Khanzeb (Pakistan Journal of Nutrition, 2013)
Solar drying of fruits, vegetables and grains is the oldest processing technique used for food preservation. In this research a flat plate solar air heater having an efficiency of 20% was used for drying onion flakes. The solar air heater assembly provides a temperature in the range of 40-50°C and humidity 10-30% in each day of drying period to the drying section. The drying section provides a total of 6 hours period per day as a suitable range for onions drying. Onions were dried and drying curves were developed for the drying kinetics of onions. The initial moisture in onions was 93% which was reduced to 5%. The moisture loss curve shows that onions lost 11% in each hour at an average. The drying curves of drying rate shows that the average drying rate of onions was 0.30 gH2O. gDM/h. Five published models (Newton, Page, Modified Page, Two-term expo and Wang) were tested to find relationship of drying curves with drying time. Among the five models Two-term expo model was the best describing drying kinetics on onions with R2 value 0.974 and Root Mean Square Error 0.447 for moisture lost and 0.953 and 0.451 for drying rate. It was concluded that flat plate solar air heater dries onions in short period of time. The quality of onions dried by a flat plate solar air heater may be better than open sun drying system. Among the five models Two-term expo model was the best describing drying kinetics on onions.